1981
DOI: 10.1073/pnas.78.10.6494
|View full text |Cite
|
Sign up to set email alerts
|

Atherosclerosis and hypertension induction by lead and cadmium ions: an effect prevented by calcium ion.

Abstract: In epidemiological studies, both positive and negative correlations have been found between cardiovascular disease and mortality and the presence of several inorganic ions in the drinking water. In an attempt to resolve this apparent disagreement, we exposed White Carneau pigeons to drinking water containing calcium (100 ppm), magnesium (30 ppm), lead (0.8 ppm), or cadmium (0.6 ppm) and used a 24-factorial design to measure the effects of these elements in atherosclerosis and hypertension. The results indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
72
0
3

Year Published

1991
1991
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 143 publications
(76 citation statements)
references
References 14 publications
1
72
0
3
Order By: Relevance
“…A large body of experimental data, both in vivo and in vitro, shows that lead increases blood pressure in several species of rats, pigeons, and dogs (13)(14)(15)(16)(17)(18). These studies have also documented increased reactivity to alpha adrenergic stimulation (14,16) and an interaction with calcium metabolism (15).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A large body of experimental data, both in vivo and in vitro, shows that lead increases blood pressure in several species of rats, pigeons, and dogs (13)(14)(15)(16)(17)(18). These studies have also documented increased reactivity to alpha adrenergic stimulation (14,16) and an interaction with calcium metabolism (15).…”
Section: Discussionmentioning
confidence: 99%
“…These studies have also documented increased reactivity to alpha adrenergic stimulation (14,16) and an interaction with calcium metabolism (15). Many ofthese studies examined several dose levels, and Victery (19) has summarized them as indicating biphasic response, with a strong effect of low-level exposure that disappears at high levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Revis et al (1980) suggested that epidemiological and clinical incidence of atherosclerosis is higher in soft-water areas than in hard-water areas. However, Revis et al (1981) concluded various studies and linked water softness to ischemic heart disease, hypertension, atherosclerosis, and to stroke. Again, however, it was also reported by Revis et al (1981) that other studies do not confirm these observations to water softness.…”
Section: Introductionmentioning
confidence: 99%
“…However, Revis et al (1981) concluded various studies and linked water softness to ischemic heart disease, hypertension, atherosclerosis, and to stroke. Again, however, it was also reported by Revis et al (1981) that other studies do not confirm these observations to water softness. Singh et al (1993) documented that F -in drinking water affects negatively or positively human health and, to far extent, influenced by the ambient temperature, alkalinity, calcium and magnesium contents of drinking water.…”
Section: Introductionmentioning
confidence: 99%